2009
DOI: 10.1093/cvr/cvp279
|View full text |Cite
|
Sign up to set email alerts
|

Protection of vascular cells from oxidative stress by proteasome inhibition depends on Nrf2

Abstract: Nrf2-dependent transcriptional activation of antioxidative enzymes is crucial for proteasome inhibitor-mediated protection of vascular cells against oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 60 publications
1
58
0
Order By: Relevance
“…8D). These genes are the targets of the transcription factor Nrf2, which is activated under oxidative stress (37,50). Continuous activation of Nrf2 is closely related to the proliferation of cancer cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…8D). These genes are the targets of the transcription factor Nrf2, which is activated under oxidative stress (37,50). Continuous activation of Nrf2 is closely related to the proliferation of cancer cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12]21 One mechanism mediating the antioxidative effects of low-dose PI in cardiovascular cells is stabilization of oxidative stress-related transcription factor nuclear erythroid 2-related factor 2. 9,21 In line with these previous in vitro observations, we found definite antioxidative effects of low-dose bortezomib treatment in hypercholesterolemic LDLR−/− mice in the present study. Serum content of lipid peroxidation by guest on May 13, 2018 http://atvb.ahajournals.org/ products, which was markedly increased in hypercholesterolemic LDLR−/2 mice compared with control diet-fed LDLR−/− mice, was significantly decreased by bortezomib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Moreover, low-dose PI was shown to enhance endothelial nitric oxide synthase expression and activity, improved endothelial function, 13 and prevented tumor necrosis factor--induced vascular dysfunction by reducing superoxide production and decreasing endothelin-1 levels in rat aortic rings. 14 We have recently shown that low-dose PI downregulates tumor necrosis factor--induced expression of VCAM-1 in endothelial cells and in a hypertensive rat model, which suggests that low-dose PI suppresses inflammatory cell adhesion in atherogenesis.…”
mentioning
confidence: 97%
“…Oxidative stress stimulus can disrupt the Nrf2/Keap1 complex and induce the translocation of Nrf2 into the nucleus. Nrf2 then binds to ARE (antioxidant-response element), which eventually results in increased expression of antioxidant genes such as heme oxygenase-1 (HO-1) and glutathione synthetic enzyme to resist oxidative stress injury [19]. Our Western blot results indicated that the CB2 receptor activation induced an increase of Akt phosphorylation, Nrf2 nuclear translocation and HO-1 expression, accompanied by cardiac function improvement, fibrosis decrease and CPC activation.…”
Section: Discussionmentioning
confidence: 71%
“…The ELISA analysis revealed that MI led to significant increases in TNF-α and IL-6, as compared with those in the sham group (TNF-α: 19 …”
Section: Am1241 Treatment Decreased Mda Tnf-α and Il-6 Levels In Thementioning
confidence: 97%